2018
DOI: 10.1038/s41598-017-18762-4
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of metformin on colorectal cancer stem cells depend on alterations in glutamine metabolism

Abstract: Metformin has been known to suppress cancer stem cells (CSCs) in some cancers. However, the differential effects of metformin on CSCs and their mechanisms have not been reported. Herein, metformin induced pAMPK activation and pS6 suppression in metformin-sensitive (HT29) cells, but not in metformin-resistant (SW620) cells. The oxygen consumption rate was higher in HT29 cells than in SW620 cells and showed a prominent decrease after metformin treatment in HT29 cells. In glutamine-depleted medium, but not in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 37 publications
2
59
0
Order By: Relevance
“…In this manuscript we show elevated GLS transcription in the invasive front of GBMs, known to contain highly invasive GSCs 35 . Previous publications reported that genetic and pharmacological inhibition of GLS attenuates stemness properties in hepatocellular, colorectal, and prostate cancer 21,23,43 . Furthermore, our group showed that the prominent route of anti-GSC therapy using γ-secretase inhibitor MRK003 targets GSC growth, in part by reducing intracellular Glu as a consequence of GLS inhibition 56 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In this manuscript we show elevated GLS transcription in the invasive front of GBMs, known to contain highly invasive GSCs 35 . Previous publications reported that genetic and pharmacological inhibition of GLS attenuates stemness properties in hepatocellular, colorectal, and prostate cancer 21,23,43 . Furthermore, our group showed that the prominent route of anti-GSC therapy using γ-secretase inhibitor MRK003 targets GSC growth, in part by reducing intracellular Glu as a consequence of GLS inhibition 56 .…”
Section: Discussionmentioning
confidence: 97%
“…Given the increasing attention of GLSi in various cancer trials, we sought to probe the target specificity of two leading GLSi compounds with the focus on their functional effects on malignant and nonmalignant stem cells. We chose C968 given its reproducibly reported therapeutic potential in many cancer studies including our own 19,21,22 , and CB839, as one of the leading clinical GLSi compounds in oncology (trial IDs: NCI-2018-00876, NCI-2019-01365, NCI-2019-00572). To our knowledge, no study has explicitly addressed the metabolic consequences of these compounds in functional assays which score their therapeutic effects preferentially as a consequence of effective target suppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that AMPK is necessary for prostate CSCs to maintain glucose balance. 396 Metformin, an antidiabetic drug that fights cancer, targets AMPK signaling to inhibit cell proliferation and metabolism in colorectal CSCs 397 and HCC stem cells. 398 Therefore, metformin may be a potential therapeutic regent by regulating the energy metabolism of CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…), driven by constitutive phosphorylation of signal transducer and activator of transcription (STAT3) , or N‐glycosyltransferase staurosporine and temperature sensitivity protein 3 (STT3)‐dependent PD‐L1 glycosylation and stabilization . Other pathways may also contribute to the regulation of PD‐L1 levels on CSCs, as demonstrated by the CSC‐suppressing effects of metformin through AMP‐activated protein kinase (AMPK) activation and inhibition of mTOR signaling . Recently, metformin has been shown to facilitate AMPK‐mediated PD‐L1 degradation in cancer cells .…”
Section: Introductionmentioning
confidence: 99%